ANTHELMINTIC ACTIVITY STUDIES ON PHERETIMA POSTHUMA WITH Cycas beddomei Dyer. LEAF, BARK, AND MALE CONE EXTRACTS - C. ALEKHYA; N. YASODAMMA; D. CHAITHRA (International Journal of Pharma and Bio Sciences, 2013)
The aim of present study is to evaluate the anthelmintic potential of aqueous, alcoholic and methanolic extracts of Cycas beddomei against Pheretima posthuma as test worms which determined the Time of Paralysis (T.P) and Time of Death (T.D) of the worms. The results indicated that the Leaf and Male cone extracts show high anthelmintic activity than bark extracts. All the three parts show good anthelmintic activity than the standard drug Albendazole. Herbal usage of the plant drug C.beddomei as an anthelmintic has been confirmed. Pith and Female cones doesn’t show any anthelmentic activity.